Thailand / Joe Cummings, Sandra Bao, Steven Martin, China Williams - Cummings, Joe
This is 10th edition guide book to travel Thailand. The Kingdom of Thailand draws more visitors than any other country in Southeast Asia with its virtually irresistible combination of brethtaking natural beauty, inspiring temples, the ruins of fabulous acient kingdoms, renowned hospitality, and robust cuisine. From the stupa0studded mountains of Mae hong Son to the verdant limestone islands of the Andaman Sea, from the pulse-pounding dance clubs of Bangkok to tranquil villages moored along the Mekong River, the country offers something for every type of traveller